2017
DOI: 10.1002/solr.201700123
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene‐Fused Perylene Diimides: New Building Blocks to Construct Non‐Fullerene Acceptors With Extremely High Open‐Circuit Voltages up to 1.26 V

Abstract: Great efforts have been devoted to seeking alternative non‐fullerene acceptors for efficient polymer solar cells (PSCs). Achieving a high open‐circuit voltage (Voc) is quite challenging but is essential for practical application. Here, pyrene‐fused perylene diimide was first used as a periphery building block to construct non‐fullerene acceptors. Due to the high‐lying lowest unoccupied molecular orbitals (LUMOs) as well as balanced transport properties, the normal devices with the acceptors exhibited ultrahigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…High carrier mobility materials have been designed to improve hole transport, reduce recombination, and enhance the FFs . New materials can be designed with better matched energy levels to increase V oc . All in all, nearly all reports on OPV cells are based on devices optimized by their PCEs .…”
Section: Introductionmentioning
confidence: 99%
“…High carrier mobility materials have been designed to improve hole transport, reduce recombination, and enhance the FFs . New materials can be designed with better matched energy levels to increase V oc . All in all, nearly all reports on OPV cells are based on devices optimized by their PCEs .…”
Section: Introductionmentioning
confidence: 99%
“…A pyrene-fused PDI derivative (TPAPPDI) possessed upshifting LUMO energy level and low bandgap. The devices exhibited a PCE of 5.10% with ultra-high V oc of up to 1.21V (Zhan et al, 2017 ). Two twisted propeller configuration PDI derivatives (TPH and TPH-Se) were developed.…”
Section: Pdi Based Small Molecule Electron Acceptorsmentioning
confidence: 99%
“…Recently, by developing novel NFSMAs with high LUMO levels and choosing suitable p-type polymers, the resulted solar cells could realize high V OC values of beyond 1.0 V (Yang et al, 2014 ; Yu et al, 2014 ; Zhang et al, 2015 , 2016 ; Baran et al, 2016 ; Fu et al, 2016 ; Li et al, 2016a ; Liu et al, 2016 ; Ni et al, 2016 ; Chen et al, 2017 ; Ding et al, 2017 ; Xiao B. et al, 2017a ; Zhan et al, 2017 ; Zhang Y. et al, 2017 ). In fact, there is always a problematic trade-off between J SC and V OC .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, there is always a problematic trade-off between J SC and V OC . Thus, very limited devices could simultaneously realize a high V OC of beyond 1.2 V and a high PCE (As shown in Figure 1 ) (Fu et al, 2016 ; Xiao B. et al, 2017a ; Zhan et al, 2017 ; Zhang Y. et al, 2017 ). For example, Xie et al reported that the OSCs containing poly(3-hexylthiophene) (P3HT) as electron donor and the oligomer F4TBT4 with four repeated fluorene and di-2-thienyl benzothiadiazole units as electron acceptor can output a high V OC above 1.2 V and a PCE of 4.12% (Fu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation